KEPUASAN WISATAWAN TERHADAP SPA TRADISIONAL BALI DI KAWASAN PARIWISATA NUSA DUA - Ida Ayu Sri Puspaadi (JURNAL KEPARIWISATAAN, 2009)
The aim of this study is to find out the tourist's satisfaction after taking the Balinese traditional spa treatments by measuring five servicedimensions. The study was conducted in the international hotels in Nusa Dua Tourism Complex. A questionnaire was administered to 30 tourists used as the sample in this research. Non-probability and accidental sampling technique were used in determining the 30 tourists participated in this study. The collected data were analyzed using Jmportance Performance. The result of the study shows that the ImportantPerformance Analysis (Cartecius Diagram) shows that the tourists' expectations and evaluation of service quality of the Balinese traditional spa treatments and products spread over the four Quarters. From 20 factors concerning tourists' expectation and satisfaction,four factors belong to quarter A, nine factors are in quarter B, six factors are in quarter C and one factor is in quarter C.